Quantitative Analysis of the Acceptance and Learning Success Instead of Flipped Classroom Teaching in a Caries Diagnosis Course for Undergraduate Students - Mozhgan Bizhang; Stefan Zimmer; Jan P. Ehlers (Hindawi Limited, 2022)
This pilot study aimed to investigate the effectiveness of a flipped classroom for undergraduate students in dentistry. The main objective was to compare the knowledge level of students before and after lectures and practice. All second-year dental students (n = 44) at Witten/Herdecke University participated in this pilot study. They took four knowledge assessments, i.e., T0: the baseline, T2a: after the online lecture (two weeks after T0), T2b: immediately after the face-to-face session, and T3: after the practical session (three weeks after T2). The students' satisfaction and self-assessment of their abilities were determined immediately after the practical session in an anonymous online questionnaire using LimeSurvey. To assess the level of knowledge, we used the Friedman and Wilcoxon-signed-rank tests with the Bonferroni correction to analyze the correct answer by comparing the results from different sessions. The students' satisfaction and self-assessment of their abilities were determined descriptively, presenting the mean and standard deviation. A significance level of p ≤ 0.05 was applied. Data from thirty-nine students regarding the level of knowledge were analyzed. There were statistically significant differences in the level of knowledge of the students at different times (p = 0.001). A total of 19.5% of students reported a problem with the flipped classroom method, and 80.5% reported no problem with this educational method. Ninety-four percent of students would like further flipped classrooms in dental education. Within the limitations of this pilot study, the results suggest that dental students benefit from the flipped classroom method and that this mode of education can be effective in introducing caries diagnosis education for undergraduate students.